1996
DOI: 10.1128/mcb.16.7.3884
|View full text |Cite
|
Sign up to set email alerts
|

The p53-Binding Protein 53BP2 Also Interacts with Bcl2 and Impedes Cell Cycle Progression at G2/M

Abstract: Using the yeast two-hybrid system, we have isolated a cDNA (designated BBP, for Bcl2-binding protein) for a protein (Bbp) that interacts with Bcl2. Bbp is identical to 53BP2, a partial clone of which was previously isolated in a two-hybrid screen for proteins that interact with p53. In this study, we show that specific interactions of Bbp/53BP2 with either Bcl2 or p53 require its ankyrin repeats and SH3 domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
132
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 55 publications
2
132
0
Order By: Relevance
“…Although recent studies have (Liu et al, 2004;Zhang et al, 2005), our results describe for the first time that a significant percentage of patients with ALL have a decreased expression of ASPP1; that lack of expression is due to hypermethylation of the gene promoter and, more importantly, that hypermethylation and downregulation of ASPP1 expression is, significantly and independently of other prognostic factors, associated with poor prognosis with a reduced DFS and OS both in children and adult ALL. The initial isolation of ASPP1 and ASPP2 proteins was performed based on two hybrid screening systems using p53 and bcl-2 as baits (Iwabuchi et al, 1994;Naumovski and Cleary, 1996). These studies identified two proteins 53BP2 and Bbp that are now recognized as truncated forms of ASPP2 (C-terminal 529 amino acids and the truncation of 123 amino acid at the N-terminal, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have (Liu et al, 2004;Zhang et al, 2005), our results describe for the first time that a significant percentage of patients with ALL have a decreased expression of ASPP1; that lack of expression is due to hypermethylation of the gene promoter and, more importantly, that hypermethylation and downregulation of ASPP1 expression is, significantly and independently of other prognostic factors, associated with poor prognosis with a reduced DFS and OS both in children and adult ALL. The initial isolation of ASPP1 and ASPP2 proteins was performed based on two hybrid screening systems using p53 and bcl-2 as baits (Iwabuchi et al, 1994;Naumovski and Cleary, 1996). These studies identified two proteins 53BP2 and Bbp that are now recognized as truncated forms of ASPP2 (C-terminal 529 amino acids and the truncation of 123 amino acid at the N-terminal, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The ANK domains in the p53-binding protein 53BP2 and in the cytoskeletal protein ankyrin are known to bind to diverse partners. More specifically, 53BP2 binds to p53, Bcl2, and the catalytic subunit of the protein phosphatase PP1 (23,24), whereas ankyrin binds to at least seven distinct membrane proteins (referenced in Ref. 25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, FLIP is up-regulated through NF-B activation, resulting in increased resistance to TNF-␣ (24). Bcl2 and p53 binding protein (BBP/53BP2) is a DNA damage-inducible protein which functions to promote apoptosis upon DNA damage (25,26). IEX-1L antideath protein has been recognized as an apoptosis inhibitor involved in NF-B-mediated cell survival (15,16).…”
Section: Expression Profiling Of Tnf-␣-modulated Nf-b-dependent Genesmentioning
confidence: 99%